Single administration of recombinant IL‐6 restores the gene expression of lipogenic enzymes in liver of fasting IL‐6‐deficient mice. (22nd February 2016) - Gavito, AL; Cabello, R; Suarez, J; Serrano, A; Pavón, F J; Vida, M; Romero, M; Pardo, V; Bautista, D; Arrabal, S; Decara, J; Cuesta, AL; et al.
Abstract : Background and Purpose: Lipogenesis is intimately controlled by hormones and cytokines as well as nutritional conditions. IL‐6 participates in the regulation of fatty acid metabolism in the liver. We investigated the role of IL‐6 in mediating fasting/re‐feeding changes in the expression of hepatic lipogenic enzymes. Experimental Approach: Gene and protein expression of lipogenic enzymes were examined in livers of wild‐type (WT) and IL‐6‐deficient (IL‐6 −/− ) mice during fasting and re‐feeding conditions. Effects of exogenous IL‐6 administration on gene expression of these enzymes were evaluated in vivo . The involvement of STAT3 in mediating these IL‐6 responses was investigated by using siRNA in human HepG2 cells. Key Results: During feeding, the up‐regulation in the hepatic expression of lipogenic genes presented similar time kinetics in WT and IL‐6 −/− mice. During fasting, expression of lipogenic genes decreased gradually over time in both strains, although the initial drop was more marked in IL‐6 −/− mice. Protein levels of hepatic lipogenic enzymes were lower in IL‐6 −/− than in WT mice at the end of the fasting period. In WT, circulating IL‐6 levels paralleled gene expression of hepatic lipogenic enzymes. IL‐6 administration in vivo and in vitro showed that IL‐6‐mediated signalling was associated with the up‐regulation of hepatic lipogenic enzyme genes. Moreover, silencing STAT3 in HepG2 cells attenuated IL‐6 mediated up‐regulation of lipogenic gene transcription levels. Conclusions and Implications: IL‐6 sustains levels of hepatic lipogenic enzymes during fasting through activation of STAT3. Our findings indicate that clinical use of STAT3‐associated signalling cytokines, particularly against steatosis, should be undertaken with caution.